Clinical patterns of hepatocellular carcinoma in nonalcoholic fatty liver disease: A multicenter prospective study. Issue 3 (14th January 2016) - Piscaglia, Fabio; Svegliati‐Baroni, Gianluca; Barchetti, Andrea; Pecorelli, Anna; Marinelli, Sara; Tiribelli, Claudio; Bellentani, Stefano; ,
Abstract : Nonalcoholic fatty liver disease (NAFLD) represents the hepatic manifestation of metabolic syndrome and may evolve into hepatocellular carcinoma (HCC). Only scanty clinical information is available on HCC in NAFLD. The aim of this multicenter observational prospective study was to assess the clinical features of patients with NAFLD‐related HCC (NAFLD‐HCC) and to compare them to those of hepatitis C virus (HCV)‐related HCC. A total of 756 patients with either NAFLD (145) or HCV‐related chronic liver disease (611) were enrolled in secondary care Italian centers. Survival was modeled according to clinical parameters, lead‐time bias, and propensity analysis. Compared to HCV, HCC in NAFLD patients had a larger volume, showed more often an infiltrative pattern, and was detected outside specific surveillance. Cirrhosis was present in only about 50% of NAFLD‐HCC patients, in contrast to the near totality of HCV‐HCC. Regardless of tumor stage, survival was significantly shorter ( P = 0.017) in patients with NAFLD‐HCC, 25.5 months (95% confidence interval 21.9‐29.1), than in those with HCV‐HCC, 33.7 months (95% confidence interval 31.9‐35.4). To eliminate possible confounders, a propensity score analysis was performed, which showed no more significant difference between the two groups. Additionally, analysis of patients within Milan criteria submitted to curative treatments did not show any difference in survival between NAFLD‐HCC and HCV‐HCC (respectively, 38.6 versus 41.0 months, P = nonsignificant) Conclusions: NAFLD‐HCC is more often detected at a later tumor stage and could arise also in the absence of cirrhosis, but after patient matching, it has a similar survival rate compared to HCV infection; a future challenge will be to identify patients with NAFLD who require more stringent surveillance in order to offer the most timely and effective treatment. (Hepatology 2016;63:827–838)